مسائل فقہیہ کی تحقیق میں تکملہ فتح الملہم کا منہج و اسلوب: In Research of Jurisprudential Issues Pattern & Style of Takmila Fath-Al-Mulhim - Dr. Zill E Huma; Dr. Shaista Jabeen (Al Manhal Research Journal, 2023)
The discipline of Hadith studies is one of the richest and exclusive discipline of knowledge as its branches extend to hundred. The religious scholars had written thousands monograph concerning Hadith interpretations and explanations. Many voluminous works appeared and existed and each of them is a commendable contribution to Hadith explanations. One of the significant works on Hadith explanations is “Takmila Fath-al-Mulhim” that is the result of scholastic efforts of many years by Mufti Muhammad Taqi Usmani. This explanation of Hadith Book Muslim was originated and finished till the “Section of Marriage” but he could not extend it to the last chapter due to his political engagements and later his demise closed the chapter. Mufti Muhammad Taqi Usmani completed the remaining work in eighteen years and nine months. During explanation of Ahadith Mufti Taqi Usmani has also discussed different jurisprudential issues and in explanation of these issues it has been seen that this explanation is pure from any type of rigidness, prejudice and descrimination. Sunni Islam is separated into four main schools of jurisprudence, namely, Hanafi, Maliki, Shafai and Hanabli. Although Taqi Usmani belongs to Hanafi school of thought but if there is found any weak point in his school of thought. He accepts it with open heart and respects the point of other scholars having different school of thought. He has explained the ahadith in a neutral, impartial and unprejudiced way. Besides this Mufti Taqi Usmani has supported and corroborated Hanafi school of thought with strong arguses and has presented solid and persuasive arguments in strengthening and justification his point of view. Moreover, he has also preferred the view point of Demos intellectuals. In this perspective some evidences have been mentioned in this article.